2018
DOI: 10.1142/s0217732318300045
|View full text |Cite
|
Sign up to set email alerts
|

The planes of satellite galaxies problem, suggested solutions, and open questions

Abstract: Satellite galaxies of the Milky Way and of the Andromeda galaxy have been found to preferentially align in significantly flattened planes of satellite galaxies, and available velocity measurements are indicative of a preference of satellites in those structures to co-orbit. There is increasing evidence that such kinematically correlated satellite planes are also present around more distant hosts. Detailed comparisons show that similarly anisotropic phase-space distributions of sub-halos are exceedingly rare in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(135 citation statements)
references
References 178 publications
5
128
2
Order By: Relevance
“…9. This confirms the expectation that the satellite galaxy phase space distribution constitutes a robust test of the cosmological model (Kroupa et al 2005;Pawlowski 2018), indicates that previous studies using dark-matter-only simulations to compare to the VPOS remain valid, and confirms earlier indications that the modelling of baryonic processes in cosmological simulations does not alleviate the planes of satellite galaxies problem (Ahmed et al 2017;Pawlowski et al 2015bPawlowski et al , 2017Pawlowski et al , 2019Shao et al 2018).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…9. This confirms the expectation that the satellite galaxy phase space distribution constitutes a robust test of the cosmological model (Kroupa et al 2005;Pawlowski 2018), indicates that previous studies using dark-matter-only simulations to compare to the VPOS remain valid, and confirms earlier indications that the modelling of baryonic processes in cosmological simulations does not alleviate the planes of satellite galaxies problem (Ahmed et al 2017;Pawlowski et al 2015bPawlowski et al , 2017Pawlowski et al , 2019Shao et al 2018).…”
Section: Resultssupporting
confidence: 88%
“…This is at odds with the high mass-to-light ratios of many of the observed dwarf satellite galaxies, unless the dark matter hypothesis is abandoned in favor of a modified gravity approach (Bílek et al 2018;Banik et al 2018). For a review of the observed satellite planes, comparison of them with cosmological simulations, and proposed solutions to the planes of satellite galaxies problem, see Pawlowski (2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is an important point because similar approaches for estimating the incidence of systems with specific properties arise in other contexts, such as estimating the rarity of 'satellite planes' (see, e.g. Pawlowski 2018).…”
Section: Comparisons With Previous Workmentioning
confidence: 99%
“…This should significantly increase the number of systems with well-resolved satellite populations which will allow for higher-precision measurements of satellite radial distributions and the variation in satellite luminosity function amplitudes (Bennet et al 2019). The expanded satellite samples should also result in better characterisation of the properties and incidence of the 'satellite planes' (Pawlowski 2018). The high abundance of bright galaxies discussed in Section 5 means that there are a large number of targets for such searches.…”
Section: Targets For Satellite Searchesmentioning
confidence: 99%
“…6; instead, it has a single (wrong) slope, and thus shows no sign of the critical acceleration a 0 . And, see also Pawlowski, 2018, who discusses the planes of satellites not being reproduced in DM simulations.…”
Section: B Mond Vs Dm: Predictions Vs After-the-fact Explanationsmentioning
confidence: 99%